Effects of freezing on soil temperature, freezing front propagation and moisture redistribution in peat: laboratory investigations - R. M. Nagare; R. A. Schincariol; W. L. Quinton; M. Hayashi (Hydrology and Earth System Sciences, 2012)
There are not many studies that report water movement in freezing peat. Soil column studies under controlled laboratory settings can help isolate and understand the effects of different factors controlling freezing of the active layer in organic covered permafrost terrain. In this study, four peat Mesocosms were subjected to temperature gradients by bringing the Mesocosm tops in contact with sub-zero air temperature while maintaining a continuously frozen layer at the bottom (proxy permafrost). Soil water movement towards the freezing front (from warmer to colder regions) was inferred from soil freezing curves, liquid water content time series and from the total water content of frozen core samples collected at the end of freezing cycle. A substantial amount of water, enough to raise the upper surface of frozen saturated soil within 15 cm of the soil surface at the end of freezing period appeared to have moved upwards during freezing. Diffusion under moisture gradients and effects of temperature on soil matric potential, at least in the initial period, appear to drive such movement as seen from analysis of freezing curves. Freezing front (separation front between soil zones containing and free of ice) propagation is controlled by latent heat for a long time during freezing. A simple conceptual model describing freezing of an organic active layer initially resembling a variable moisture landscape is proposed based upon the results of this study. The results of this study will help in understanding, and ultimately forecasting, the hydrologic response of wetland-dominated terrain underlain by discontinuous permafrost.